Effectiveness of natural and commercial dressing material In the second and third stages pressure ulcer management - Ajee K L , Naveen Chandra , A Prescillal (Migration Letters, 2024)
Pressure ulcers are a highly debilitating issue that commonly accompanies catastrophic conditions like Spinal cord injuries (SCI), Cerebrovascular accidents, and others. Wound care is necessary for second and third-stage pressure ulcers, and whenever possible, the wound dressing–if there is one—should be degradable. The study aimed to assess the efficacy of Coloplast, Coloplast silver biatin, amniotic membrane, and egg white dressing in treating second and third-stage pressure ulcers. Methods: In this double-blinded randomized controlled design, 120 randomly selected second and third-stage pressure ulcers of seronegative patients for HIV and HBsAg, that do not require surgical intervention were studied. The wound condition was assessed at the beginning of the study, with every change of dressing for a maximum of 21 days. PUSH 3.0 was used to assess the pressure ulcer healing process and SPSS 20 was used for statistical analysis. Result: The study group consisted of 97% males and 75% were between 18 -37 years of age. Head injury (48%) and Spinal cord Injury (42%) were the leading cause of immobility. All physiological parameters of all samples, like vital signs, blood reports, wound swabs, and urine culture reports, were within the standard limit. All were seronegative at the beginning of the study and at the time of discharge. All four types of dressing materials were equally significant (p< .05) in healing pressure ulcers. No complications developed during hospitalization with any of the four dressing materials used in the study. There was no change in the antibiotics or no apparent signs of infection present. A multiple comparison with the Kruskal Wallis test revealed no significant change in the number of days taken to heal the pressure ulcers in four groups of samples. Discussion: This research suggests that egg white dressing and amniotic membrane have an equivalent impact on the healing process of pressure ulcers as commercial dressing materials such as coloplast silver biatin and coloplast (comfeel). Many studies corroborate these results. Conclusion: Though all four interventions had uneventful healing, Pressure ulcer management with commercial dressing materials is highly expensive. Amniotic membranes and egg whites are readily available, and these natural dressing materials are biodegradable and eco-friendly.